Experiences of technology-rich innovation in European schools within the Open Discovery Space project - Sonia PEINADO; José Miguel MOTA; Anke BERNS; Manuel PALOMO-DUARTE; Juan Manuel DODERO; Stefano MARTELLOS; Rosa DORAN; Aušra LINGYTE; Christine J. ARNOLD; Kerstin BISSINGER; Orlin KOUZOV; Eleni CHELIOTI; et al. (Ediciones Universidad de Salamanca, 2015)
The Open Discovery Space (ODS) project was conceived to introduce innovative resource-based teaching and learning practices in European schools, to promote the creation of communities between European school members and to boost the demand for open educational resources among teachers. After 3 years of applying the ODS innovation model, more than 2,000 European schools have carried out diverse experiences of technology-rich innovation to achieve the project aims. This paper describes the experiences and results of ODS in 7 different European countries, along with the international activities that aim at expanding the scope of the project beyond the European limits.